Preference for Male Facial Masculinity as a Function of Mental Rotation Ability in Gay and Bisexual Men, but Not in Heterosexual Men and Women in China - Zheng, Lijun (Frontiers in Psychology, 2019)
This study examined the association between mental rotation ability and facial masculinity preference in gay and bisexual men in China. The participants (436 gay/bisexual men, 132 heterosexual men and 254 heterosexual women) completed an online Shepard and Metzler-type mental rotation task and a forced-choice preference task of ten pairs of masculinized/feminized male faces. The results revealed that mental rotation ability was significantly associated with preference for masculinized faces in both gay and bisexual men. There were no significant correlations between mental rotation ability and facial masculinity preference in both heterosexual men and women. The findings imply homogamy in partner preference in gay and bisexual men in terms of masculinity.